Current Rise of Extensive Drug Resistant Salmonella Cases in a Tertiary Care Hospital of Karachi, Pakistan (Medical Forum Monthly, 2023)
Objective: To assess antimicrobial surveillance of bacteremia isolates of Salmonella typhi and paratyphi.Study Design: A descriptive retrospective observational studyPlace and Duration of Study: This study was conducted at the Department of Microbiology, Dow University Research and Referral Laboratory from April 2021 to, March 2022.Materials and Methods: Blood culture Reports from April 2021 to, March 2022 was obtained from laboratory data. About 8329 laboratory reports were collected. The data transferred to Microsoft excel and final analysis was performed by using Statistical Package for Social Science (SPSS) version-20. The categorical variables were interpreted as frequencies and percentages of isolated organism and their antibiotic susceptibility pattern was presented graphically.Results: Majority of the typhoid cases were seen in children less than 15 years of age (mean value and standard deviation for age statistically was 9.6 and 9.2 respectively). Males were more affected (59%). There is no association of age and gender with the occurrence of typhoid fever as the p-value was more than 0.05. Total of 8329 cases were suspected for typhoid during April 2021 to March 2022, out of which 699 (8%) cases were positive for typhoid. Among 699 positive typhoid cases, 71% were extremely drug resistant while 15% cases were multi drug resistant. Maximum confirmed cases of typhoid were reported during the month of September to November. Out of 699 confirmed typhoid cases, only 173 (24%) cases were having known vaccination status.Conclusion: The susceptibility of Salmonella typhi and paratyphi against recommended antibiotics is 8% while majority of cases were having extremely drug resistant (71%) followed by multi drug resistant strain (15%). The most commonly affected age group was children under 15 years of age.